2020
DOI: 10.1177/0890207020962328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sociometer theory in children’s everyday lives: Inclusion, but not exclusion by peers at school is related to within-day change in self-esteem

Abstract: Sociometer theory proposes that a person’s self-esteem is a permanent monitor of perceived social inclusion and exclusion in a given situation. Despite this within-person perspective, respective research in children’s everyday lives is lacking. In three intensive longitudinal studies, we examined whether children’s self-esteem was associated with social inclusion and exclusion by peers at school. Based on sociometer theory, we expected social inclusion to positively predict self-esteem and social exclusion to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 72 publications
(184 reference statements)
2
16
0
Order By: Relevance
“…They may also hold motivation of selfprotection and then tend to avoid or neglect information that may threat their self-image (Sedikides et al, 2016). Supporting this proposal, Schmidt and colleges (Schmidt et al, 2020) found that for school-aged children, it is social inclusion, not exclusion that predict their evening self-esteem.…”
Section: Discussionmentioning
confidence: 93%
“…They may also hold motivation of selfprotection and then tend to avoid or neglect information that may threat their self-image (Sedikides et al, 2016). Supporting this proposal, Schmidt and colleges (Schmidt et al, 2020) found that for school-aged children, it is social inclusion, not exclusion that predict their evening self-esteem.…”
Section: Discussionmentioning
confidence: 93%
“…Each time participants reported a social interaction during the ESM period, they were asked to what degree they rated the social interaction as positive and as interesting on a 10-point scale from 0 ( not at all ) to 10 ( very ). Assessments of social inclusion have varied widely across studies, ranging from explicit measures of rejection to measures of relationship or interaction quality (Denissen et al, 2008; Schmidt et al, 2021). Overall, the sociometer effect appears to be robust across these different assessment methods (Harris & Orth, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Based on evolutionary notions, one key ingredient boosting self-esteem should be the perceptions of social belonging and inclusion (Baumeister & Leary, 1995). Empirical research based on samples from Western industrialized countries highlights that perceptions of social inclusion and social interaction quality are indeed related to state self-esteem, both in experimental settings (Leary et al, 1995; Pass et al, 2010; Thomaes et al, 2010) and in real-life situations (Denissen et al, 2008; Schmidt et al, 2021). We will refer to the association between perceptions of social inclusion and self-esteem as self-esteem reactivity 2 .…”
Section: Trait Self-esteem Development: Mean-level Trends and Rank-or...mentioning
confidence: 99%
“…Data of this study was collected within the SASCHA project (Social and Academic School transition CHAllenges), which comprised two intensive measurement bursts and a follow-up assessment. Prior work using data from this study has targeted the association between social relatedness and well-being or self-esteem (Schmidt et al, in press; Schmidt, Dirk, et al, 2020; Schmidt, Neubauer, et al, 2020), and between daily goal orientations and daily experiences of success and failure (Neubauer, Schmidt, et al, 2020). Thus far, no other work has utilized information on children’s sleep collected in this project.…”
Section: Methodsmentioning
confidence: 99%